2020
DOI: 10.1016/j.actamat.2020.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Slip band characteristics in the presence of grain boundaries in nickel-based superalloy

Abstract: Shear strain profiles along slip bands in a modified Rolls-Royce nickel superalloy (RR1000) were analyzed for a tensile sample deformed by 2%. The strain increased with distance away from a grain boundary (GB), with maximum shear strain towards the center of the grain, indicating that dislocation nucleation generally occurred in the grain interior. The strain gradients in the neighborhood of the GBs were quantified and generally correlated with rotation about the active slip system line direction. This leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…stress follows a r -1/2 relationship where r is the distance from the start of the pile-up). This has been experimentally verified in hexagon [16,17] and cubic [54] alloys An attempt to calculate the strain and stress fields directly adjacent to blocked slip bands observed in this work was made, using the HR-EBSD elastic strain measurements. However, it was difficult to extract any useful information due to both the spatial resolution at which the HR-EBSD measurements were taken and the more complex slip behaviour than the simple slip band to grain boundary behaviour observed in the studies in titanium [16,17] or nickel [54].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…stress follows a r -1/2 relationship where r is the distance from the start of the pile-up). This has been experimentally verified in hexagon [16,17] and cubic [54] alloys An attempt to calculate the strain and stress fields directly adjacent to blocked slip bands observed in this work was made, using the HR-EBSD elastic strain measurements. However, it was difficult to extract any useful information due to both the spatial resolution at which the HR-EBSD measurements were taken and the more complex slip behaviour than the simple slip band to grain boundary behaviour observed in the studies in titanium [16,17] or nickel [54].…”
Section: Discussionmentioning
confidence: 61%
“…This has been experimentally verified in hexagon [16,17] and cubic [54] alloys An attempt to calculate the strain and stress fields directly adjacent to blocked slip bands observed in this work was made, using the HR-EBSD elastic strain measurements. However, it was difficult to extract any useful information due to both the spatial resolution at which the HR-EBSD measurements were taken and the more complex slip behaviour than the simple slip band to grain boundary behaviour observed in the studies in titanium [16,17] or nickel [54]. The spatial resolution of the HR-EBSD in this work was optimised to cover a large area in order to capture a range of slip behaviour, using a step size of 0.5 μm, larger than the 0.2 μm used in [16,17] but in keeping with the work of others [14,31,55].…”
Section: Discussionmentioning
confidence: 61%
“…Once the two active slip systems across the GB or TB were identified, different metrics can be determined to assess whether they are able to predict slip transfer or blocking. Among them, the Luster-Morris parameter m and the residual Burgers vector ∆b have been used previously [11,13,16,17] in metallic polycrystals. It should be noted that If slip traces were only visible only in one grain across the boundary but not in the other, these GB or TB were not included in the analysis because it was not possible to identify the active slip plane in the latter grain.…”
Section: Resultsmentioning
confidence: 99%
“…They could not, however, provide a criteria because of the experimental scatter, which was attributed to the influence of the twist angle θ which cannot be determined from the EBSD information for regular GB. Finally, Sperry et al [17] also combined EBSD with high resolution digital image correlation to study slip transfer in another Ni-based superalloy. They concluded that slip transfer in regular GB was associated with low misorientation angles and it was maximum when m = 0.78 in twin boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of dislocations with GBs as well as GB sliding, e.g., during creep, can be assessed using molecular dynamics. [90][91][92][93][94] Cleavage energy and (partial) cohesive energy are calculated to gauge the resistance against GB decohesion. [36][37][38]43] Table 1 provides a brief summary of first-principles calculations on B in Ni.…”
Section: Segregationmentioning
confidence: 99%